S-Quinolin-2-ylmethyldithiocarbazate. - How, Fiona Ni Foong; Watkin, David J.; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim (International Union of Crystallography, 2007)
In the title compound, C11H11N2S2, there is an intramolecular N-H...N [2.778 (2) Å] hydrogen bond linking the quinoline N atom and the imino N atom. The planar quinoline ring system forms an angle of 67.7 (1)° with the dithiocarbazate group. Bond angles for both S-C-S [115.66 (8)°] and N-C-S [119.05 (11)°] are comparable with cis-trans S-methyldithiocarbazate but differ from those found in trans-cis S-methyldithiocarbazate and trans-cis S-benzyldithiocarbazate. This is due to the N-H...N hydrogen bond that exists only in the cis-trans conformation found for the title compound.